Pengaruh Jenis Pemanis Terhadap Karakteristik Fisik Granul Effervescent Daun Lidah Buaya (Aloe vera L.) - Rahmatul Mutia Mutia; Hamsinah Hamsinah; Amelia Sari; Ernita Silviana; Burdah Burdah; Rima Hayati (Poltekkes Kemenkes Bengkulu, 2026)
Aloe vera L. has considerable potential as a natural ingredient for oral preparations; however, the inherent bitterness of its leaf powder limits patient acceptability. Effervescent granules were selected to improve convenience and palatability, in which sweeteners may influence both taste and physical performance. This study aimed to evaluate the effect of sweetener type on the physical characteristics of Aloe vera effervescent granules. Granules were prepared by wet granulation using aspartame (F1) and stevia (F2). Evaluations included organoleptic properties, moisture content, flow time, angle of repose, and dispersion time. Statistical analysis was performed using the Mann–Whitney U test for moisture content and Welch’s t-test for other parameters. Both formulations met general quality requirements for effervescent granules. No significant differences were observed in moisture content and dispersion time (p > 0.05). However, flow time and angle of repose differed significantly (p < 0.05). F1 showed faster flow time (1.55 ± 0.05 s) and lower angle of repose (20.40 ± 1.07°) compared to F2 (2.30 ± 0.26 s; 24.70 ± 1.35°), indicating better flowability. These findings suggest that sweetener type significantly influences granule flow properties but not moisture stability or dispersion performance